1987
DOI: 10.1128/jb.169.2.660-665.1987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bromoethanesulfonate-resistant mutants of Methanococcus voltae: evidence of a coenzyme M transport system

Abstract: Mutants of Methanococcus voltae were isolated that were resistant to the coenzyme M (CoM; 2-mercaptoethanesulfonic acid) analog 2-bromoethanesulfonic acid (BES). The mutants displayed a reduced ability to accumulate [35S]BES relative to the sensitive parental strain. BES inhibited methane production from CH3-S-CoM in cell extracts prepared from wild-type sensitive or resistant strains. BES uptake requwred the presence of both CO2 and H2 and was inhibited by N-ethylmaleimide and several reagents that are known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The coenzyme M (CoM) analog BES is a potent inhibitor of the enzyme methyl-CoM reductase that catalyzes the final step in methane production. In earlier studies, M. voltae strains incapable of either BES or CoM uptake were isolated as BES R mutants (37). However, the mutated gene(s) in these strains were never identified.…”
Section: Use Of Mini-mar Elements To Isolate M Acetivorans Mutants Rmentioning
confidence: 99%
“…The coenzyme M (CoM) analog BES is a potent inhibitor of the enzyme methyl-CoM reductase that catalyzes the final step in methane production. In earlier studies, M. voltae strains incapable of either BES or CoM uptake were isolated as BES R mutants (37). However, the mutated gene(s) in these strains were never identified.…”
Section: Use Of Mini-mar Elements To Isolate M Acetivorans Mutants Rmentioning
confidence: 99%
“…In the experiments shown, the chromosomal DNA used for electroporation of the his-12 auxotroph was partially digested with the restriction enzyme EcoRI; however, partial digestion with HindIlI gave similar levels of electroporation as did undigested DNA. For electroporation of the pur-J aux- (12). BES, a methyl-CoM analog, is an inhibitor of methyl reductase (5), an enzyme complex responsible for the final steps of methanogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that this marine methanogen is capable of taking up 2-mercaptoethanesulfonic acid (HS-CoM, coenzyme M) via an energy-dependent, carrier-mediated uptake system (4,12). HS-CoM is an intermediate in methanogenesis and carries a methyl moiety in the form of methyl-S-CoM, the terminal carrier of C1 in the process of methane formation (6,14).…”
mentioning
confidence: 99%
“…The methanococci are attractive subjects for molecular biology experiments and as candidate species for developing archaebacterial genetics. They grow relatively quickly, form colonies on agar-solidified defined media (1,8,21), contain plasmids (23), can be transformed (3), give rise to mutants (7,16), and can be lysed for DNA isolation simply by the addition of detergents (12) proCJ 19 tsx purEl galK2 trp-3 hisA4 argG36 rpsL xyl-Imtl-I ilvA6 thr-J met-12 (6; obtained from R. Curtiss III).Transformants of E. coli X760 which grew at 37°C on plates containing supplemented M9-glucose minimal-salts medium lacking histidine but containing 100 ,ug of ampicillin per ml were selected (2). One such transformant contained plasmid pET9301 which was shown by DNA sequencing (14) to contain a 2,155-base-pair (bp) HindIII-BamHI-generated fragment of M. thermolithotrophicus genomic DNA (Fig.…”
mentioning
confidence: 99%
“…The methanococci are attractive subjects for molecular biology experiments and as candidate species for developing archaebacterial genetics. They grow relatively quickly, form colonies on agar-solidified defined media (1,8,21), contain plasmids (23), can be transformed (3), give rise to mutants (7,16), and can be lysed for DNA isolation simply by the addition of detergents (12) proCJ 19 tsx purEl galK2 trp-3 hisA4 argG36 rpsL xyl-Imtl-I ilvA6 thr-J met-12 (6; obtained from R. Curtiss III).…”
mentioning
confidence: 99%